The Influence of Personal Attributes, Adversity Quotient with Self Efficacy as a Mediation Variable on Entrepreneurial Intention - Siti Nur azizah; Uswatun Hasanah (FEB UNWIKU PURWOKERTO, 2021)
This study aims to determine the effect of personal attributes, adversity quotient and self-efficacy that affect the entrepreneurial intention of Putra Bangsa University Kebumen students. The population in this study were students of the regular class management study program. The sampling technique used non-probability sampling. Methods of data collection using a questionnaire. Data were analyzed using SPSS 22.0. The results showed that personal attributes and adversity quotient had a positive and significant effect on self-efficacy. Personal attributes, adversity quotient, and self efficacy partially have a positive and significant influence on entrepreneurial interest. Personal attributes through self-efficacy have a positive and significant influence on interest in entrepreneurship and adversity quotient through self-efficacy has a positive and significant influence on entrepreneurial interest. The conclusion of the study is that there is an influence of personal attributes (personality) and adversity quotient on the entrepreneurial interest, either directly or indirectly.